Effect of PEX, a Noncatalytic Metalloproteinase Fragment with Integrin-Binding Activity, on Experimental Chlamydophila pneumoniae Infection - Caronzolo, Dario (American Society for Microbiology, 2006)
Chlamydophila pneumoniae is a pathogen that is involved in acute and chronic respiratory infections and that is associated with asthma and coronary artery diseases. In this study, we evaluated the effects of PEX, a noncatalytic metalloproteinase fragment with integrin-binding activity, against experimental infections caused by C. pneumoniae. Moreover, we investigated the relationships between C. pneumoniae and α(v)β(3) integrin functions in order to explain the possible mechanism of action of PEX both in vitro and in vivo. For the in vitro experiments, HeLa cells were infected with C. pneumoniae and treated with either PEX or azithromycin. The results obtained with PEX were not significantly different (P > 0.05) from those achieved with azithromycin. Similar results were also obtained in a lung infection model. Male C57BL/J6 mice inoculated intranasally with 10(6) inclusion-forming units of C. pneumoniae were treated with either PEX or azithromycin plus rifampin. Infected mice treated with PEX showed a marked decrease in C. pneumoniae counts versus those for the controls; this finding did not differ significantly (P > 0.05) from the results observed for the antibiotic-treated group. Integrin α(v)β(3) plays an important role in C. pneumoniae infection. Blockage of integrin activation led to a significant inhibition of C. pneumoniae infection in HeLa cells. Moreover, CHO(DHFR) α(v)β(3)-expressing cells were significantly (P < 0.001) more susceptible to C. pneumoniae infection than CHO(DHFR) cells. These results offer new perspectives on the treatment of C. pneumoniae infection and indicate that α(v)β(3) could be a promising target for new agents developed for activity against this pathogen.